Preoperative Cervical Smear Cytology and Clinicopathologic Characteristics in Endometrial Cancer - Kubra Cakar Yilmaz; Kevser Arkan; Asli Tugce Sarisoy; Sunullah Soysal (Journal of Clinical Medicine, 2026)
Objectives: The endometrium and cervix share a common Müllerian origin and may exhibit overlapping biological responses to oncogenic stimuli. However, the clinical significance of preoperative cervical cytology in patients with endometrial cancer remains unclear. This study aimed to investigate the association between preoperative cervical smear cytology and clinicopathologic characteristics, with particular emphasis on advanced FIGO stage (III–IV) as the primary outcome. Methods: This retrospective cohort study included 154 patients who underwent primary surgery for histologically confirmed endometrial cancer. Preoperative cervical smear cytology was classified according to the Bethesda System into four categories: normal, low-grade, high-grade, and malignant. For subgroup analyses, low-grade, high-grade, and malignant cytology results were combined and compared with normal cytology. FIGO stage was analyzed both as individual stages (IA–IV) and as early-stage (I–II) versus advanced-stage (III–IV) disease, where appropriate. Continuous variables were summarized as mean ± standard deviation or median (interquartile range), while categorical variables were expressed as n (%). Group comparisons were performed using the Pearson chi-square test or Fisher’s exact test, as appropriate, and a two-sided p value < 0.05 was considered statistically significant. Results: A total of 154 patients with endometrial cancer were included in the analysis. Preoperative cervical smear cytology was normal in 140 patients (90.9%), low-grade in 6 (3.9%), high-grade in 3 (1.9%), and malignant in 5 (3.2%). Comparison across cytology categories demonstrated a significant association between smear cytology and FIGO stage (p < 0.001), with high-grade and malignant cytology occurring more frequently in patients with advanced-stage disease. Vaginal cuff involvement was also significantly associated with smear cytology (p = 0.001), whereas no significant associations were observed for myometrial invasion, lymphovascular space invasion, cervical stromal involvement, tubo-ovarian involvement, omental involvement, or lymph node metastasis. Subgroup analysis comparing normal and abnormal cytology yielded similar findings, confirming significant associations with FIGO stage (p < 0.001) and vaginal cuff involvement (p = 0.002). In a multivariable model additionally including cervical cytology, LVSI and deep myometrial invasion were independent predictors of advanced stage (AUC = 0.888), whereas cytology was not statistically significant after adjustment (OR 4.51, p = 0.076) and showed poor standalone diagnostic performance (AUC = 0.564, sensitivity 19.4%, specificity 93.5%). All patients with vaginal cuff involvement had advanced-stage disease (Fisher’s exact p < 0.001). The cytology–FIGO stage association was not significant in postmenopausal (p = 0.065) or endometrioid-only (p = 1.00) subgroup analyses. Conclusions: Abnormal preoperative cervical smear cytology was significantly associated with advanced FIGO stage and vaginal cuff involvement in patients with endometrial cancer. These findings suggest that cervical cytological abnormalities may reflect overall disease extent rather than individual histopathological risk factors. Given the retrospective design and the limited number of patients with abnormal cytology, these findings should be interpreted cautiously and validated in larger prospective studies. However, cytology was not an independent predictor of advanced stage after multivariable adjustment and performed poorly as a standalone diagnostic marker, suggesting it should not be used alone to assess disease extent.